Designing and building earthquake warning system with Arduino and web-based SES60 SLP sensor - Edidas Edidas; Rusnardi Rahmat Putra (Institute of Advanced Engineering and Science, 2022)
Indonesia is a country that is crossed by a world ring of fire that has the potential for earthquakes and tsunamis. An earthquake is an occurrence of shaking the ground due to the sudden release of energy into the earth. Since earthquakes occur within an undetermined period, we need a device to detect earthquake vibrations as early as possible within few seconds and announce real-time warning information on the website. The monitor screen displays a flat, a slightly increasing, the alarm displays a sound